Tuberculose bovina: diagnóstico intradérmico e exames complementares em propriedade de exploração leiteira - Souza, Mariana Assunção de (2013)
The aim of this study was to evaluate the incidence of tuberculosis in a cattle herd by the cervical comparative intradermal tuberculin test (ITT), and analyze the efficiency of complementary diagnostic methods in confirming the infection. The study was conducted on a breeding dairy farm in the city of Perdizes MG. Tuberculin test was performed in 164 cattle, of which 40 were positive and slaughtered. The macroscopic post mortem inspection of carcasses was followed by the collection of nasal swabs, blood and tissue samples (liver, lung and mediastinal lymph node) for PCR tests, ELISA and histopatology with Hematoxylin-Eosin (HE) and Ziehl-Neelsen (ZN) respectively. Of the 164 cattle analysed by ITT, 41 (25%) were positive, 29 (17.68%) inconclusive and 94 (57.32%) negative. Of the 40 cattle slaughtered, 22 (55%) carcasses had macroscopic lesions suggestive of tuberculosis, 14 (35%) in the mediastinal lymph nodes, seven (17.5%) in the liver and six (15%) in the lung. The histopathology HE identified 13 (32.5%) carcasses with histological changes, six (15%) in the mediastinal lymph nodes, five (12.5%) in the liver and three (7.5%) in the lung. At ZN, the presence of acid-fast bacilli was not detected in any of samples tested. The ELISA/IDEXX identified one (2.5%) animal reagent, and the PCR test detected DNA of M. bovis in one (2.5%) cow. Being a dairy herd, the occurrence of tuberculosis may represent a zoonotic risk. The ITT should already be a routine test required for the farms that sells milk or meat, because it recognizes recent infections, often not detected by other diagnostic methods.